Anti-urease therapy: a targeted approach to mitigating antibiotic resistance in Helicobacter pylori while preserving the gut microflora - Christina Almarmouri; Mohammed I. El-Gamal; Mohamed Haider; Mohamad Hamad; Shamsul Qumar; Merylin Sebastian; Rose Ghemrawi; Jibran Sualeh Muhammad; Christophe Burucoa; Ghalia Khoder (Gut Pathogens)
Abstract The global rise in antibiotic resistance has posed significant challenges to the effective management of Helicobacter pylori (H. pylori), a gastric pathogen linked to chronic gastritis, peptic ulcers, and gastric cancer. Conventional antibiotic therapies, while effective, face significant challenges, such as increasing antibiotic resistance, high recurrence rates, and adverse effects such as gut microflora dysbiosis. These limitations have driven the exploration of alternative antibiotic-free therapies, including the use of plant-based compounds, probiotics, nanoparticles, phage therapy, antimicrobial peptides, and H. pylori vaccines. Among these, urease-targeted therapy has shown particular promise. Urease enables the survival and colonization of H. pylori by neutralizing stomach acidity. Targeting this urease without disrupting beneficial gut microflora offers a selective mechanism to impair H. pylori, due to the absence of this enzyme in most of the human gut microbiome. In this review, we highlight advancements and limitations in the field of antibiotic-free therapies, with a particular focus on anti-urease strategies. We explore the structural and functional characteristics of urease, its role in H. pylori pathogenesis, and its potential as a therapeutic target. For the first time, we provide a comprehensive analysis of natural, semisynthetic, and synthetic anti-urease compounds, emphasizing their mechanisms of action, efficacy, and safety profiles. Advances in silico, in vitro, and in vivo studies have identified several promising anti-urease compounds with high specificity and minimal toxicity. By focusing on urease inhibition as a targeted strategy, this review underscores its potential to overcome antibiotic resistance while minimizing gut dysbiosis and improving the outcomes of H. pylori infection treatment. Graphical Abstract